2006
DOI: 10.1080/09537100500220729
|View full text |Cite
|
Sign up to set email alerts
|

The mean platelet volume in subjects with impaired fasting glucose

Abstract: Mean platelet volume (MPV), a determinant of platelet function, is a newly emerging risk factor for atherothrombosis. Impaired fasting glucose (IFG) is probably a frequent glycemic disorder in the general population and is considered as a prediabetic state. The present study was designed to evaluate MPV in subjects with IFG compared with diabetic patients and normoglycemic control subjects. We selected 50 patients with type 2 diabetes mellitus, 50 subjects with IFG, and 50 normoglycemic healthy subjects matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 16 publications
5
71
3
2
Order By: Relevance
“…Alternatively this may suggest that platelet activation is related to glycemic control [38,37]. Hyperglycemia occur non enzymatic glycation of proteins on the surface of the platelets, which decrease membrane fluidity and increase its reactivity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively this may suggest that platelet activation is related to glycemic control [38,37]. Hyperglycemia occur non enzymatic glycation of proteins on the surface of the platelets, which decrease membrane fluidity and increase its reactivity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the platelets with normal volume, large platelets appear to show higher level of metabolic activity. Therefore, studies have shown raised TxA2 and low prostacyclin (PG12) levels, leading to vasoconstriction in both maternal and fetal circulation (Çoban et al, 2006;Crowther et al, 2005) Elevated MPV is recognized as an important marker of raised blood sugar level in GDM patients and it is held responsible for the microvascular and macrovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in these variables may be involved in the natural history of vascular disease. Larger and functionally more reactive platelets have been found in diabetics and also prediabetics [26,27]. Although platelet counts are normal in diabetics, multiple studies offer evidence of enhanced activation or increased platelet activity in patients with T2DM [9].…”
Section: Discussionmentioning
confidence: 99%